Surface reconstruction-based selenium antimony sulfide thin film solar cell and preparation method thereof

By performing in-situ surface reconstruction on the surface of the selenium antimony sulfide film and optimizing the antimony sulfide layer by chemical water bath method, the problem of low efficiency of the selenium antimony sulfide film solar cell is solved, and efficient photoelectric conversion efficiency improvement and process simplification is achieved.

CN119153548APending Publication Date: 2024-12-17NANKAI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411291522.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The photoelectric conversion efficiency of selenium antimony sulfide thin-film solar cells is mainly due to the large open circuit voltage loss and the difficulty of existing hydrothermal methods to observe and control the film growth process, which limits its industrial application.

Method used

The chemical water bath method was used to carry out in situ surface reconstruction on the surface of the selenium antimony sulfide film. By depositing an antimony sulfide layer on a transparent conductive glass substrate, the antimony potassium fermented and sodium thiosulfate were used as antimony and sulfur sources, the Antimony sulfide layer, optimize the film structure to improve efficiency.

Benefits of technology

Effectively passivate interface defects, reduce open circuit voltage loss, improve carrier separation and transmission efficiency, improve photoelectric conversion efficiency to 9.93%, and simplify process flow and reduce costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119153548A_ABST
    Figure CN119153548A_ABST
Patent Text Reader

Abstract

The invention discloses a surface reconstruction-based selenium antimony sulfide thin film solar cell and a preparation method thereof. Antimony potassium tartrate and sodium thiosulfate are put into deionized water to be stirred, the concentration of antimony potassium tartrate is 17.14-32.5 g / L, and the concentration of sodium thiosulfate is 14.28-32.5 g / L; putting the selenium antimony sulfide thin film obtained by reaction after complete dissolution into a reaction bottle, and obtaining the selenium antimony sulfide thin film with a reconstructed surface after 0.5-2 hours in a water bath kettle; and flushing the obtained thin film with deionized water, blow-drying the thin film with a nitrogen gun, and annealing the thin film on a 350-380 DEG C heating stage in a glove box to obtain the selenium antimony sulfide light absorption layer. Transparent conductive glass (FTO) is used as a substrate, the thin film solar cell with the device structure of FTO / cadmium sulfide electron transport layer / selenium antimony sulfide light absorption layer / surface reconstructed antimony sulfide layer / hole transport layer / gold electrode is prepared, and the photoelectric conversion efficiency is 9.93%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of thin film solar cell devices, and in particular proposes a method for preparing a precursor thin film based on in-situ surface reconstruction for preparing high-quality antimony selenium sulfide thin film cells by a chemical water bath method. In particular, a method for improving antimony selenium sulfide thin film solar cells based on surface reconstruction and a preparation method thereof are proposed. Background Art

[0002] In the field of thin-film batteries, cadmium telluride, copper indium gallium selenide and perovskite thin-film batteries have achieved photoelectric conversion efficiencies of 22.6%, 23.6% and 26.15%, respectively. However, in practical applications, in addition to considering high photoelectric conversion efficiency, the cost of the battery and its environmental friendliness must also be considered. Since Cd is a toxic metal element, In, Ga and Te are all scarce elements, the production cost of the battery is increased invisibly, which is greatly restricted in the industrialization process. In order to meet the energy needs of human society, the development of low-cost, high-quality, green and stable solar cells is imminent. Antimony-based thin-film solar cells, including antimony selenide, antimony sulfide and antimony selenium sulfide, are considered as one of the candidate materials for the light absorption layer of thin-film batteries due to their rich element reserves, high absorption coefficient, non-toxicity and environmental friendliness, and have been widely studied. As the light absorption layer material of solar cells, antimony selenide has the following advantages: (1) Antimony selenide has a quasi-one-dimensional band structure, and its grain boundaries have strong self-healing ability; (2) The absorption coefficient is high, which can reach 10 in the visible light range. 5 cm -1 ; (3) By adjusting the Se / S ratio, the band gap of antimony selenide can be adjusted between 1.1-1.7 eV; (4) The theoretical limit efficiency can reach 32%. As a highly promising thin-film solar cell, antimony selenide has received more and more attention.

[0003] At present, the highest photoelectric conversion efficiency of antimony selenide sulfide is still far behind that of cadmium telluride thin film batteries. The main reason is that the open circuit voltage loss of antimony selenide sulfide thin film batteries is too large. Therefore, appropriate optimization treatment of the surface of antimony selenide sulfide thin film will help passivate interface defects, improve carrier utilization efficiency, and reduce carrier recombination. At present, the hydrothermal method is widely used to prepare antimony selenide sulfide thin films. The hydrothermal method needs to be carried out in a high-temperature and high-pressure reactor to prepare thin films. It is impossible to observe and regulate the reaction process, so it is difficult to observe and control the growth process of the film.

[0004] The chemical water bath method used in the present invention has the advantages of lower reaction temperature, more open reaction environment, simpler reaction equipment, lower cost, easier observation and control of the reaction process, and safer reaction. Therefore, the chemical water bath method for preparing more efficient antimony selenium sulfide thin film solar cells has a broader application prospect. Summary of the invention

[0005] The invention aims at antimony selenium sulfide solar cells prepared by a chemical water bath method and proposes a method for improving the efficiency of antimony selenium sulfide thin film solar cells based on surface reconstruction.

[0006] The technical solution of the present invention is as follows:

[0007] A surface reconstruction-based antimony selenide sulfide thin film solar cell; using transparent conductive glass FTO as a substrate, a layer of antimony sulfide layer is reconstructed on the surface of the antimony selenide sulfide absorption layer.

[0008] The method for improving antimony selenide sulfide thin film solar cells based on surface reconstruction and reconstructing an antimony sulfide layer on the surface is that after the antimony selenide sulfide layer is deposited in a water bath, the antimony sulfide layer is deposited on the obtained film. The specific process of antimony sulfide layer deposition is: potassium antimony tartrate is used as the antimony source and sodium thiosulfate is used as the sulfur source to prepare the antimony sulfide surface reconstruction layer.

[0009] The method for constructing an antimony sulfide layer of an antimony selenide sulfide thin film solar cell based on surface reconstruction is as follows: a certain amount of potassium antimony tartrate and sodium thiosulfate are placed in deionized water for stirring, wherein the concentration of potassium antimony tartrate is 17.14-32.5 g / L, and the concentration of sodium thiosulfate is 14.28-32.5 g / L. After stirring until completely dissolved, pour into a reactor, and place the antimony selenide sulfide film obtained by the above reaction into a reaction bottle, and place it in a water bath for 0.5-2 hours to obtain a surface reconstructed antimony selenide sulfide film; the obtained film is first rinsed with deionized water and blown dry with a nitrogen gun, and placed on a 350-380°C hot stage in a glove box for annealing for 5-15 minutes to obtain an antimony selenide sulfide light absorption layer.

[0010] The specific instructions are as follows:

[0011] The antimony selenide sulfide thin film battery in the present invention uses transparent conductive glass (FTO) as a substrate, and prepares a thin film solar cell with a device structure of FTO / cadmium sulfide electron transport layer / antimony selenide sulfide absorption layer / surface reconstructed antimony sulfide layer / hole transport layer / gold electrode.

[0012] The existing antimony selenide sulfide battery structure is FTO / electron transport layer / antimony selenide sulfide light absorption layer / hole transport layer / gold electrode.

[0013] The main content of the present invention is to reconstruct an antimony sulfide layer on the surface of the antimony selenide sulfide absorption layer on the basis of the existing one.

[0014] The present invention is to prepare an antimony sulfide layer on the surface of the light absorbing layer based on the original antimony selenide sulfide film, and the other layer structures remain unchanged. Figure 1 The antimony sulfide layer shown in (a) is the main content of the present invention. Figure 1(b) as shown.

[0015] The present invention is a method for preparing an antimony selenide sulfide thin film solar cell based on surface reconstruction to improve the antimony sulfide layer, comprising the following steps:

[0016] (1) ultrasonically cleaning the FTO substrate using a cleaning agent, acetone, isopropanol, anhydrous ethanol, and deionized water for 15-30 minutes each;

[0017] (2) A cadmium sulfide electron transport layer is prepared by chemical water bath deposition, wherein 150-165 mL of deionized water, 17.5-22.5 mL of a 1.5 mmol cadmium sulfate solution, 9.5-11.25 mL of a 15 mmol thiourea solution, and 25-30

[0018] mL of ammonia water was put into a beaker and stirred evenly, and the FTO that had been cleaned in one step was placed in it. It was deposited in a constant temperature water bath at 60-66°C for 9-13 minutes, and then rinsed with deionized water and dried with a nitrogen gun to obtain a cadmium sulfide electron transport layer.

[0019] (3) Antimony selenide film was prepared using potassium antimony tartrate as the antimony source, sodium thiosulfate as the sulfur source, and sodium selenosulfate as the selenium source. Sodium selenosulfate was prepared by mixing deionized water, sodium sulfite and selenium powder and then subjecting them to a hydrothermal reaction. First, 35-40 mL of deionized water was placed in a small beaker and stirred. Then, 20-30 mM potassium antimony tartrate, 140-160 mM sodium thiosulfate pentahydrate and 7-10 mL of selenium source were added to the small beaker. After stirring until slightly turbid, the mixture was poured into a reaction bottle. The sample obtained in the previous step was placed in the reaction bottle, and then placed in a 95°C water bath for reaction for 2-4 hours to obtain an antimony selenide film. Finally, the obtained film was rinsed with deionized water and dried with a nitrogen gun, and then placed on a 350-380°C hot plate in a glove box for annealing for 5-15 minutes to obtain an antimony selenide light-absorbing layer.

[0020] (4) Preparation of hole transport layer: We use Spiro-OMeTAD as the hole transport layer. The preparation process is as follows: First, dissolve 65-75 mg of Spiro-OMeTAD powder in 1.5-2.5 mL of chlorobenzene, add 25-30 μL of 4-tert-butylpyridine (tBP) and 15-20 μL of 520 mg / mL Li-TFSI solution, and oscillate evenly to obtain the Spiro-OMeTAD solution. Then, spin coat it on the surface of the antimony selenide sulfide absorption layer at a speed of 3000 r / s and a rotation time of 30 s. Finally, place it on a 100°C hot stage for annealing for 10 minutes to obtain the Spiro-OMeTAD hole transport layer. (5) Preparation of gold electrode: The present invention uses thermal evaporation to prepare Au electrode. The sample obtained in the previous step is placed in the evaporation equipment and the vacuum degree is reduced to 5.0×10 -4 Next, Au with a thickness of about 70-100 nm was evaporated. After the evaporation, 6 layers with an area of ​​0.105 cm 2 of batteries.

[0021] The above is the entire preparation process of the antimony selenide sulfide thin film solar cell in the present invention.

[0022] The present invention is about the construction of the antimony sulfide layer, and the preparation process and method of other layers can adopt all methods of the prior art.

[0023] The present invention achieves the effect of mutual diffusion and redistribution of selenium and sulfur elements on the surface by in-situ reconstruction of a layer of antimony sulfide on the surface of antimony selenide, effectively passivates defects at the interface, reduces open circuit voltage loss, effectively inhibits carrier recombination, improves carrier separation and transmission efficiency, and makes it have a longer carrier life, and finally prepares an antimony selenide sulfide thin film solar cell with a photoelectric conversion efficiency of 9.93%.

[0024] The cell efficiency obtained by the invention is the highest device efficiency among antimony selenium sulfide thin film solar cells prepared by a chemical water bath method.

[0025] The present invention has the following advantages:

[0026] The present invention makes full use of the advantage that the reaction process of the chemical water bath method is easy to observe and control, and specifically proposes a method for in-situ surface reconstruction of an antimony sulfide layer.

[0027] The present invention achieves the effect of mutual diffusion and redistribution of selenium and sulfur elements on the surface by in-situ reconstruction of a layer of antimony sulfide on the surface of antimony selenide, effectively passivates selenium vacancies and antimony-related defects at the interface, reduces open-circuit voltage loss, effectively inhibits carrier recombination, improves carrier separation and transmission efficiency, and makes it have a longer carrier lifetime, and finally prepares an antimony selenium sulfide thin-film solar cell with a photoelectric conversion efficiency of 9.93%.

[0028] The surface reconstruction method used in the present invention effectively solves the problem of low open circuit voltage of the chemical water bath method, and plays a key role in improving device performance. The method used in the present invention has the characteristics of simple operation, short time consumption, good repeatability, strong applicability, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 (a) is a flow chart of the preparation of an antimony selenide sulfide solar cell containing an antimony sulfide layer;

[0030] Figure 1 (b) is a flow chart for preparing an antimony selenide sulfide solar cell without an antimony sulfide layer;

[0031] Figure 2 Current density-voltage curves of solar cells prepared for the present invention with different deposition times (0h, 0.5h, 1h and 2h) of antimony sulfide;

[0032] Figure 3 (a) is the surface morphology of the antimony selenide sulfide film without antimony sulfide layer;

[0033] Figure 3 (b) is the morphology of the antimony sulfide film deposited for 0.5h;

[0034] Figure 3 (c) is the morphology of the antimony sulfide film deposited for 1 h;

[0035] Figure 3 (d) is the morphology of the antimony sulfide film deposited for 2 hours;

[0036] Figure 3 (e) is a cross-sectional morphology of a film without an antimony sulfide layer;

[0037] Figure 3 (f) is the cross-sectional morphology of the antimony sulfide film deposited for 0.5 h;

[0038] Figure 3 (g) is the cross-sectional morphology of the antimony sulfide film deposited for 1 h;

[0039] Figure 3 (h) is the cross-sectional morphology of the antimony sulfide film deposited for 2 hours. DETAILED DESCRIPTION

[0040] The solution of the present invention will be described in more detail below in conjunction with specific implementation cases.

[0041] Example 1

[0042] The preparation process of this embodiment is as follows:

[0043] 1) Substrate cleaning: First, the transparent conductive oxide (FTO) substrate was ultrasonically cleaned with clean water, acetone, isopropanol and anhydrous ethanol for 30 minutes respectively, and then dried with nitrogen for standby use.

[0044] 2) Preparation of cadmium sulfide electron transport layer: After a certain amount of chromium sulfate solution, ammonia water and thiourea solution are stirred evenly in a beaker, the sample obtained in the previous step is placed in a beaker and placed in a water bath at 60°C. After sedimentation for 9 minutes, the sample is taken out and the surface floating matter is rinsed off with deionized water and blown dry with nitrogen to obtain a cadmium sulfide electron transport layer.

[0045] 3) Preparation of antimony selenide sulfide light-absorbing layer: Sb 2 (S,Se) 3 The film was prepared by chemical bath deposition. The reaction process was as follows: 35 mL of deionized water was placed in a beaker and stirred, and then 20 mM of antimony source (potassium antimony tartrate, K 2 Sb 2 C 8 H 4 O 12 ·3H 2 O), 140 mM sulfur source (sodium thiosulfate, Na 2 S 2 O 3 ·5H 2 O) and 7 mL of selenium source (synthesized by hydrothermal reaction of sodium sulfite and selenium powder), then stir until slightly turbid and pour it into a reaction bottle, and place the sample containing the CdS layer obtained in the previous step in it, and put it in a water bath at 95°C to react for 2 hours.

[0046] 4) Then, potassium antimony tartrate was used as the antimony source and sodium thiosulfate was used as the sulfur source to deposit the antimony sulfide surface reconstruction layer, wherein the concentration of potassium antimony tartrate was 17.14 g / L and the concentration of sodium thiosulfate was 14.28 g / L. After 1 hour, a water-bath deposited antimony selenide sulfide film was obtained. After the reaction was completed, the sample was rinsed with deionized water and dried with a nitrogen gun. Finally, the dried Sb 2 (S,Se) 3 The film was placed on a hot plate in a glove box and annealed for 5 min at different temperatures (0°C, 300°C, 350°C, 380°C, 400°C) to obtain Sb 2 (S,Se) 3 Absorption layer.

[0047] 5) Preparation of hole transport layer: Spiro-OMeTAD was used as the hole transport layer. The preparation process was as follows: First, 65 mg of Spiro-OMeTAD powder was dissolved in 1.5 mL of chlorobenzene, and 25 μL of 4-tert-butylpyridine (tBP) and 15 μL of 520 mg / mL Li-TFSI solution were added. After oscillation, the Spiro-OMeTAD solution was obtained. The solution was then spin-coated on the surface of the antimony selenide sulfide absorption layer at a rotation speed of 3000 r / s for 30 seconds. Finally, it was placed at 100°C.

[0048] Annealing on a hot stage for 10 min gave the Spiro-OMeTAD hole transport layer.

[0049] 6) Preparation of gold electrode: The present invention adopts thermal evaporation to prepare Au electrode. The sample obtained in the previous step is placed in the evaporation equipment. When the vacuum degree drops to 5.0×10 -4 Next, Au with a thickness of about 70 nm was evaporated. After the evaporation, 6 layers with an area of ​​0.105 cm 2 of batteries.

[0050] In order to obtain the most suitable annealing temperature for antimony sulfide, in this embodiment, we fixed the annealing time to 10 minutes, and performed annealing at 0°C, 300°C, 350°C, 380°C and 400°C respectively. The device performance changes are as follows:

[0051] Table 1 shows the performance of antimony selenide sulfide solar cells prepared under different glove box annealing temperature conditions for solar cells containing antimony sulfide layers.

[0052]

[0053] As can be seen from Table 1, for the present invention, when the glove box annealing temperature is 370°C, the best device performance is obtained, and the maximum battery efficiency is 9.5%. 350-380°C is selected as the best annealing temperature for the present invention.

[0054] Example 2

[0055] The preparation process of this embodiment is as follows:

[0056] 1) Substrate cleaning: First, the transparent conductive oxide (FTO) substrate was ultrasonically cleaned with clean water, acetone, isopropanol and anhydrous ethanol for 20 minutes respectively, and then dried with nitrogen for standby use.

[0057] 2) Preparation of cadmium sulfide electron transport layer: After a certain amount of chromium sulfate solution, ammonia water and thiourea solution are stirred evenly in a beaker, the sample obtained in the previous step is placed in a beaker and placed in a water bath at 62°C. After sedimentation for 11 minutes, the sample is taken out and the surface floating matter is rinsed off with deionized water and dried with nitrogen to obtain a cadmium sulfide electron transport layer.

[0058] 3) Preparation of antimony selenide sulfide light-absorbing layer: Sb 2 (S,Se) 3 The film was prepared by chemical bath deposition. The reaction process was as follows: 36 mL of deionized water was placed in a beaker and stirred, and then 23 mM of antimony source (potassium antimony tartrate, K 2 Sb 2 C 8 H 4 O 12 ·3H 2 O), 147 mM sulfur source (sodium thiosulfate, Na 2 S 2 O 3 ·5H 2 O) and 8 mL of selenium source (synthesized by hydrothermal reaction of sodium sulfite and selenium powder), then stir until slightly turbid and pour it into a reaction bottle, and place the sample containing the CdS layer obtained in the previous step in it, and put it in a water bath at 95°C to react for 2 hours.

[0059] 4) Then, potassium antimony tartrate was used as the antimony source and sodium thiosulfate was used as the sulfur source to deposit the antimony sulfide surface reconstruction layer, wherein the concentration of potassium antimony tartrate was 22.26 g / L and the concentration of sodium thiosulfate was 20.35 g / L. After 0.5-2 hours, the surface reconstructed antimony selenide sulfide film was obtained. After the reaction was completed, the sample was rinsed with deionized water and dried with a nitrogen gun. Finally, the dried Sb 2 (S,

[0060] Se) 3 The film was placed on a 380°C hot plate in a glove box and annealed for 10 min to obtain Sb 2 (S,Se) 3 Absorption layer.

[0061] 5) Preparation of hole transport layer: Spiro-OMeTAD was used as the hole transport layer. The preparation process was as follows: First, 69 mg of Spiro-OMeTAD powder was dissolved in 1.9 mL of chlorobenzene, and 27 μL of 4-tert-butylpyridine (tBP) and 17 μL of 520 mg / mL Li-TFSI solution were added. After oscillation, the Spiro-OMeTAD solution was obtained. The solution was then spin-coated on the surface of the antimony selenide sulfide absorption layer at a rotation speed of 3000 r / s for 30 seconds. Finally, it was placed at 100°C.

[0062] Annealing on a hot stage for 10 min gave the Spiro-OMeTAD hole transport layer.

[0063] 6) Preparation of gold electrode: The present invention adopts thermal evaporation to prepare Au electrode. The sample obtained in the previous step is placed in the evaporation equipment. When the vacuum degree drops to 5.0×10 -4 Next, Au with a thickness of about 80 nm was evaporated. After the evaporation, 6 layers with an area of ​​0.105 cm 2 of batteries.

[0064] Table 2 shows the performance of antimony sulfide selenide solar cell devices based on different antimony sulfide surface reconstruction times. 0 is an antimony sulfide selenide cell without surface reconstruction, 0.5, 1, and 2 are antimony sulfide selenide cells with antimony sulfide deposition times of 0.5h, 1h, and 2h, respectively. Finally, the device data was obtained by testing under a solar simulator (AM 1.5), and its current density-voltage curve is shown in Figure 2 When antimony sulfide was deposited for 1 h, the battery performance was the best, with an efficiency of 9.93% and an open circuit voltage of 526 mV.

[0065] sample Open circuit voltage(V) <![CDATA[Short-circuit current (mA / cm 2 )]]> Fill factor (%) Conversion efficiency (%) 0 0.448 28.31 61.30 7.77 0.5 0.480 27.84 62.36 8.34 1 0.526 26.91 70.14 9.93 2 0.531 27.03 55.88 8.03

[0066] Example 3

[0067] The preparation process of this embodiment is as follows:

[0068] 1) Substrate cleaning: First, the transparent conductive oxide (FTO) substrate was ultrasonically cleaned with clean water, acetone, isopropanol and anhydrous ethanol for 15 minutes respectively, and then dried with nitrogen for standby use.

[0069] 2) Preparation of cadmium sulfide electron transport layer: After a certain amount of chromium sulfate solution, ammonia water and thiourea solution are stirred evenly in a beaker, the sample obtained in the previous step is placed in a beaker and placed in a water bath at 64°C. After sedimentation for 12 minutes, the sample is taken out and the surface floating matter is rinsed off with deionized water and blown dry with nitrogen to obtain a cadmium sulfide electron transport layer.

[0070] 3) Preparation of antimony selenide sulfide light-absorbing layer: Sb 2 (S,Se) 3 The film was prepared by chemical bath deposition. The reaction process was as follows: 38 mL of deionized water was placed in a beaker and stirred, and then 26 mM of antimony source (potassium antimony tartrate, K 2 Sb 2 C 8 H 4 O 12 ·3H 2 O), 153 mM sulfur source (sodium thiosulfate, Na 2 S2 O 3 ·5H 2 O) and 9 mL of selenium source (synthesized by hydrothermal reaction of sodium sulfite and selenium powder), then stir until slightly turbid and pour it into a reaction bottle, and place the sample containing the CdS layer obtained in the previous step in it, and put it in a water bath at 95°C to react for 3 hours.

[0071] 4) Then, potassium antimony tartrate was used as the antimony source and sodium thiosulfate was used as the sulfur source to deposit the antimony sulfide surface reconstruction layer, wherein the concentration of potassium antimony tartrate was 27.38 g / L and the concentration of sodium thiosulfate was 26.42 g / L. After 0.5-2 hours, the surface reconstructed antimony selenide sulfide film was obtained. After the reaction was completed, the sample was rinsed with deionized water and dried with a nitrogen gun. Finally, the dried Sb 2 (S,

[0072] Se) 3 The film was placed on a 350°C hot plate in a glove box and annealed for 15 min to obtain Sb 2 (S,Se) 3 Absorption layer.

[0073] 5) Preparation of hole transport layer: Spiro-OMeTAD was used as the hole transport layer. The preparation process was as follows: First, 72 mg of Spiro-OMeTAD powder was dissolved in 2.2 mL of chlorobenzene, and 29 μL of 4-tert-butylpyridine (tBP) and 19 μL of 520 mg / mL Li-TFSI solution were added. After oscillation, the Spiro-OMeTAD solution was obtained, and then it was spin-coated on the surface of the antimony selenide sulfide absorption layer at a speed of 3000 r / s for 30 seconds. Finally, it was placed at 100°C.

[0074] Annealing on a hot stage for 10 min gave the Spiro-OMeTAD hole transport layer.

[0075] 6) Preparation of gold electrode: The present invention adopts thermal evaporation to prepare Au electrode. The sample obtained in the previous step is placed in the evaporation equipment. When the vacuum degree drops to 5.0×10 -4 Next, Au with a thickness of about 90 nm was evaporated. After the evaporation, 6 layers with an area of ​​0.105 cm 2 of batteries.

[0076] Attached Figure 3 The morphology of the surface and cross section of the antimony sulfide selenide film obtained based on different antimony sulfide surface reconstruction times. 0 is an antimony sulfide selenide cell without surface reconstruction, 0.5, 1, and 2 are antimony sulfide selenide cells with antimony sulfide deposition times of 0.5h, 1h, and 2h, respectively. It can be seen from the cross-sectional morphology that with the increase of antimony sulfide deposition time, the thickness of antimony sulfide also increases. Figure 2This indicates that the optimal antimony sulfide thickness is reached after 1 hour of deposition, and the device performance is optimal.

[0077] Example 4

[0078] The preparation process of this embodiment is as follows:

[0079] 1) Substrate cleaning: First, the transparent conductive oxide (FTO) substrate was ultrasonically cleaned with clean water, acetone, isopropanol and anhydrous ethanol for 30 minutes respectively, and then dried with nitrogen for standby use.

[0080] 2) Preparation of cadmium sulfide electron transport layer: After a certain amount of chromium sulfate solution, ammonia water and thiourea solution are stirred evenly in a beaker, the sample obtained in the previous step is placed in a beaker and placed in a water bath at 66°C. After sedimentation for 13 minutes, the sample is taken out and the surface floating matter is rinsed off with deionized water and blown dry with nitrogen to obtain a cadmium sulfide electron transport layer.

[0081] 3) Preparation of antimony selenide sulfide light-absorbing layer: Sb 2 (S,Se) 3 The film was prepared by chemical bath deposition. The reaction process was as follows: 40 mL of deionized water was placed in a beaker and stirred, and then 30 mM of antimony source (potassium antimony tartrate, K 2 Sb 2 C 8 H 4 O 12 ·3H 2 O), 160 mM sulfur source (sodium thiosulfate, Na 2 S 2 O 3 ·5H 2 O) and 10 mL of selenium source (synthesized by hydrothermal reaction of sodium sulfite and selenium powder), then stir until slightly turbid and pour it into a reaction bottle, and place the sample containing the CdS layer obtained in the previous step in it, and put it in a water bath at 95°C to react for 4 hours.

[0082] 4) Then, potassium antimony tartrate was used as the antimony source and sodium thiosulfate was used as the sulfur source to deposit the antimony sulfide surface reconstruction layer, wherein the concentration of potassium antimony tartrate was 32.5 g / L and the concentration of sodium thiosulfate was 32.5 g / L. After 2 hours, the surface reconstructed antimony selenide sulfide film was obtained. After the reaction was completed, the sample was rinsed with deionized water and dried with a nitrogen gun. Finally, the dried Sb 2 (S,Se) 3 The film was placed on a 370°C hot plate in a glove box and annealed for 5, 10, and 15 min, respectively, to obtain Sb 2 (S,Se) 3 Absorption layer.

[0083] 5) Preparation of hole transport layer: Spiro-OMeTAD was used as the hole transport layer. The preparation process was as follows: First, 75 mg of Spiro-OMeTAD powder was dissolved in 2.5 mL of chlorobenzene, and 30 μL of 4-tert-butylpyridine (tBP) and 20 μL of 520 mg / mL Li-TFSI solution were added. After oscillation, the Spiro-OMeTAD solution was obtained. The solution was then spin-coated on the surface of the antimony selenide sulfide absorption layer at a rotation speed of 3000 r / s for 30 seconds. Finally, it was placed at 100°C.

[0084] Annealing on a hot stage for 10 min gave the Spiro-OMeTAD hole transport layer.

[0085] 6) Preparation of gold electrode: The present invention adopts thermal evaporation to prepare Au electrode. The sample obtained in the previous step is placed in the evaporation equipment. When the vacuum degree drops to 5.0×10 -4 Next, Au with a thickness of about 100 nm was evaporated. After the evaporation, 6 layers with an area of ​​0.105 cm 2 of batteries.

[0086] In order to verify the optimal annealing time applicable to the present invention, the glove box was set up and the optimal temperature was 370°C. The annealing time was different (5min, 10min and 15min), and the device performance shown below was obtained:

[0087] Table 3 shows the device performance obtained by annealing the antimony sulfide-containing film for different times.

[0088] Time (min) Open circuit voltage(V) <![CDATA[Short-circuit current (mA / cm 2 )]]> Fill factor (%) Conversion efficiency (%) 5 0.497 27.35 67.67 9.20 10 0.496 27.96 66.67 9.25 15 0.480 28.19 65.27 8.84

[0089] The results show that, according to the present invention, better device performance can be obtained when the annealing time is 5-10 minutes.

Claims

1. A method for improving antimony selenide sulfide thin film solar cells based on surface reconstruction; Its characteristics are: Using transparent conductive glass FTO as the substrate, a layer of antimony sulfide layer is reconstructed on the surface of the antimony selenide sulfide absorption layer.

2. The antimony selenide sulfide thin film solar cell based on surface reconstruction as claimed in claim 1; Its characteristics are: The method for reconstructing a layer of antimony sulfide on the surface is to deposit an antimony sulfide layer on the obtained film after depositing an antimony selenide sulfide layer in a water bath. The specific process of antimony sulfide layer deposition is: using potassium antimony tartrate as the antimony source and sodium thiosulfate as the sulfur source to prepare the antimony sulfide surface reconstruction layer.

3. The method for constructing an antimony sulfide layer of an antimony selenide sulfide thin film solar cell based on surface reconstruction as claimed in claim 2; Its characteristics are A certain amount of potassium antimony tartrate and sodium thiosulfate are placed in deionized water and stirred, wherein the concentration of potassium antimony tartrate is 17.14-32.5 g / L, and the concentration of sodium thiosulfate is 14.28-32.5 g / L; after stirring until completely dissolved, pour into a reactor, and put the antimony selenium sulfide film obtained by the previous reaction into a reaction bottle, and place it in a water bath for 0.5-2 hours to obtain a surface reconstructed antimony selenium sulfide film; the obtained film is first rinsed with deionized water and blown dry with a nitrogen gun, and placed on a 350-380°C hot stage in a glove box for annealing for 5-15 minutes to obtain an antimony selenium sulfide light-absorbing layer.